Estimation of Carbon Stock in Mangrove Seedlings and Sediment in EEA Bagek Kembar, West Lombok - Pahrurrozi, Pahrurrozi; Hadiprayitno, Gito; Suyantri, Eni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Mangrove are coastal ecosystems that play a crucial role in maintaining environmental stability, protecting shorelines, and providing essential habitats for diverse species of flora and fauna. Mangrove ecosystems also play a vital role in mitigating climate change by absorbing and storing atmospheric carbon. This study was conducted with the objective of estimate the carbon stock in mangrove seedlings and sediments within the Essential Ecosystem Area (EEA) of Bagek Kembar, Sekotong, West Lombok. Mangrove seedlings sampling was conducted using the destructive (harvesting) method and analyzed in accordance with the Indonesia National Standard (SNI), while mangrove sediments sampling was carried out using a corer and analyzed using the Loss on Ignition (LOI) method. The results showed that natural mangroves had seedlings carbon stock of 3.44 tons C/ha, whereas rehabilitated mangroves had seedlings carbon stock of 2.95 tons C/ha. Carbon stock at sediment in natural mangroves was 591.49 Mg/ha, and for sediments at rehabilitated mangroves was 575.39 Mg/ha. The average seedlings carbon stock in the EEA Bagek Kembar Sekotong West Lombok was 3.19 tons C/ha, while the average sediments carbon stock was 583.41 Mg/ha. These findings highlight the significant carbon storage potential of mangroves ecosystems, particulary in seedlings and sediments. Although mangrove seedling possess relatively small biomass, they make a meaningful contribution to future carbon stock.